Acute Kidney Injury, Immune Thrombocytopenic Purpura, and the Infection That Binds Them Together: Disseminated Histoplasmosis. (December 2017) - Sethi, Pooja; Treece, Jennifer; Onweni, Chidinma; Pai, Vandana; Arikapudi, Sowminya; Kallur, Lakshmi; Kohli, Varun; Moorman, Jonathan
Untreated human immunodeficiency virus (HIV) can be complicated by opportunistic infections, including disseminated histoplasmosis (DH). Although endemic to portions of the United States and usually benign, DH can rarely act as an opportunistic infection in immunocompromised patients presenting with uncommon complications such as acute kidney injury and idiopathic thrombocytopenic purpura. We report a rare presentation of DH presenting with acute kidney injury and immune thrombocytopenic purpura in an immunocompromised patient with HIV.